2020
DOI: 10.1111/acem.14122
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Maltreatment in Infants and Young Children Presenting With Fractures: Does Age Matter?

Abstract: Objectives Child abuse is a significant cause of morbidity and mortality in preverbal children who cannot explain their injuries. Fractures are among the most common injuries associated with abuse but of themselves fractures may not be recognized as abusive until a comprehensive child abuse evaluation is completed, often prompted by other signs or subjective features. We sought to determine which children presenting with rib or long‐bone fractures should undergo a routine abuse evaluation based on age. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In fact, the same code set was applied by another study of children under 18 years old without justification (Schilling, 2020). Likewise, rib fracture was identified as suggestive of physical abuse for children under two (Högberg, 2018; Lindberg, 2015), five (Schnitzer et al, 2011), and 18 (Matone, 2018; Schilling, 2020), while a meta-analysis on fracture in young children and infants and child maltreatment found that children under the age of three presenting with a rib fracture should raise the awareness for a child abuse evaluation (Mitchell et al, 2021). Because relevant codes for suspected maltreatment vary with age, future research proposing coding schemes should explicitly discuss upper and lower age limits for each diagnosis code.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the same code set was applied by another study of children under 18 years old without justification (Schilling, 2020). Likewise, rib fracture was identified as suggestive of physical abuse for children under two (Högberg, 2018; Lindberg, 2015), five (Schnitzer et al, 2011), and 18 (Matone, 2018; Schilling, 2020), while a meta-analysis on fracture in young children and infants and child maltreatment found that children under the age of three presenting with a rib fracture should raise the awareness for a child abuse evaluation (Mitchell et al, 2021). Because relevant codes for suspected maltreatment vary with age, future research proposing coding schemes should explicitly discuss upper and lower age limits for each diagnosis code.…”
Section: Discussionmentioning
confidence: 99%
“…However, certain fracture patterns (CML, posterior rib fractures, scapular fractures, spinous process fractures, sternal fractures) have a much higher specificity for abuse than other fracture patterns (e.g., clavicular fractures, long bone shaft fractures) [77]. When excluding motor vehicle collisions, rib fractures were associated with abuse in 96% of cases in children < 3 years of age [78]. Furthermore, age < 12 months, rather than anatomic location, was the only risk factor associated with increased incidence of abuse in the setting of rib fractures [79].…”
Section: Skeletal Injuriesmentioning
confidence: 98%
“…Furthermore, age < 12 months, rather than anatomic location, was the only risk factor associated with increased incidence of abuse in the setting of rib fractures [79]. Similarly, long bone fractures of the humerus or femur have a high incidence (25-48%) in abused children and especially infants [73,78,80]. Skull fractures, on the other hand, are the most common presenting fracture and are associated with abuse in < 20% of cases, especially when simple and linear [73].…”
Section: Skeletal Injuriesmentioning
confidence: 99%
“…25,26 The correlation of CPA and isolated humerus or femur fracture in a child younger than 18 months was a finding by members of the PTS guidelines committee. 27…”
Section: Imagingmentioning
confidence: 99%